Relooking at the Roles of Translanguaging in English as a Foreign Language Classes for Multilingual Learners: Practices and Implications - Wang, Ping (Frontiers in Psychology, 2022)
The use of translanguaging pedagogy rather than favoring English-only teaching pit those who hold monolingual ideology in foreign language pedagogy. A study of English as a foreign language (EFL) for multilingual students showed that embracing translanguaging appeared compelling that it emerged in Neidi Xinjiang Classes (NXC) in China. After reviewing the concepts of translanguaging, this writing presents the translanguaging theory and translanguaging pedagogy. Guided by translanguaging lenses and stances, a longitudinal case study was carried out to look into the EFL pedagogy in NXC. The focal data was heavily drawn from reflective interviews and classroom observations. The data analyses were particularly paid on the triangulation of data with the interviews and classroom observational data. The findings indicate the students made full use of the affordances to do translanguaging practices while a few EFL teachers with the monolingual ideology still violated with English-only constraints against the background of the multilingual turn. Therefore, the conclusion builds on dynamic multilingual stances to identify the significance of enabling the presence of translanguaging pedagogy.